2018
DOI: 10.3389/fneur.2018.00185
|View full text |Cite
|
Sign up to set email alerts
|

The Crucial Changes of Sit-to-Stand Phases in Subacute Stroke Survivors Identified by Movement Decomposition Analysis

Abstract: ObjectiveThe aim of this study was to detect the key changes during sit-to-stand (STS) movement cycle in hemiparetic stroke survivors using a five-phase kinematic and kinetic analysis.MethodsTwenty-five subacute stroke survivors and 17 age-matched healthy adults participated in this study. The kinematic and kinetic parameters during STS cycle were measured using three-dimensional motion analysis system with force plates. The five standard phases of STS cycle were identified by six timing transitional points.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…As the events of hesitation (maximum forward velocity and maximum upward acceleration) both occur around the end of Phase 1 of movement, the flexion momentum, these data indicate that hesitation is likely contributing factor to the longer Phase 1 of movement seen in STS compared to STW. A prolonged Phase 1 has previously been described in studies examining STW in stroke survivors when compared to healthy adults; here stroke survivors spent a greater amount in Phase 1 because of increased time spent in hip flexion (7). A lengthened Phase 1 of movement is also seen in older adults, when compared to younger adults attributed to an increased angle of trunk flexion (27).…”
Section: The Differences Between Movement Fluidity and Duration Of Phases Between Sts And Stwsupporting
confidence: 55%
See 2 more Smart Citations
“…As the events of hesitation (maximum forward velocity and maximum upward acceleration) both occur around the end of Phase 1 of movement, the flexion momentum, these data indicate that hesitation is likely contributing factor to the longer Phase 1 of movement seen in STS compared to STW. A prolonged Phase 1 has previously been described in studies examining STW in stroke survivors when compared to healthy adults; here stroke survivors spent a greater amount in Phase 1 because of increased time spent in hip flexion (7). A lengthened Phase 1 of movement is also seen in older adults, when compared to younger adults attributed to an increased angle of trunk flexion (27).…”
Section: The Differences Between Movement Fluidity and Duration Of Phases Between Sts And Stwsupporting
confidence: 55%
“…(2) between 3 and 42 days after stroke, either infarct or hemorrhage; (3) considered to be fit for rehabilitation, having peripheral oxygen saturations 90%+ on air, resting pulse <101 beats/min; (4) able to take at least three steps with abnormal initial foot contact and/or decreased ability to take full body weight through the paretic lower limb during stance; with the assistance of up to two people if required; (5) able to follow a 1-stage command; and (6) free from contractures or loss of skin integrity in lower limb. (7) For inclusion in the secondary analysis presented here, participants were those who met the above criteria, 1-7, and who were: (8) able to complete a STS and STW task at the outcome measurement time point (∼6 weeks after start of the intervention phase) without physical assistance from another person, object or aid (e.g., walking stick).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with a stroke, longer total time as well as changes at the initial phase and at the end of hip and knee extension phase were observed. The maximal hip flexion was lower during the rising phase from a seated position on the affected side in the stroke group [ 44 ]. Patients with end stage renal disease undergoing hemodialysis have high morbidity and mortality due to multiple causes.…”
Section: Discussionmentioning
confidence: 99%
“…The STS transition is regarded as one of the most demanding daily physical activities [ 8 ], associated with a high level of energy expenditure [ 9 ] and joint stress [ 10 ]. The STS performance can be adversely affected by multiple clinical conditions [ 11 , 12 ], such as aging [ 13 , 14 , 15 ]. It has been reported that people who have difficulty in reaching the bipedal position are more likely to fall [ 16 ].…”
Section: Introductionmentioning
confidence: 99%